Looming the Future - Agurto Zegarra, Angela María (2025)
This essay is based on the source critique of a contemporary photograph depicting weavers from Chinchero, Peru. Its aim is to analyze how traditional looms play the role of persistent technology that sustains cultural identity and female agency for the weaving communities in Cusco. Drawing on concepts from Science and Technology Studies (STS), it argues that the loom is not merely a tool, but a community-based technology central to cultural identity and social cohesion. The analysis reveals that the loom, as a community-based technology, enables a sociotechnical relationship for cultural practices, where identity becomes central and reaffirmed through weaving. More significantly, the practice of weaving fos-ters female agency. The essay concludes that these looms act as persistent technologies, dynamically rewriting cultural heritage to integrate the present while preserving intergenerational practices, thus ensuring the community’s resilience and economic adaptation amidst modern challenges.